The Profiling of DNA Methylation and Its Regulation on Divergent Tenderness in Angus Beef Cattle - Zhao, Chunping; Ji, Guanyu; Carrillo, José A.; Li, Yaokun; Tian, Fei; Baldwin, Ransom L.; Zan, Linsen; Song, Jiuzhou (Frontiers in Genetics, 2020)
Beef is an essential food source in the world. Beef quality, especially tenderness, has a significant impact on consumer satisfaction and industry profit. Many types of research to date have focused on the exploration of physiological and developmental mechanisms of beef tenderness. Still, the role and impact of DNA methylation status on beef tenderness have yet to be elucidated. In this study, we exhaustively analyzed the DNA methylation status in divergent tenderness observed in Angus beef. We characterized the methylation profiles related to beef tenderness and explored methylation distributions on the whole genome. As a result, differentially methylated regions (DMRs) associated with tenderness and toughness of beef were identified. Importantly, we annotated these DMRs on the bovine genome and explored bio-pathways of underlying genes and methylation biomarkers in beef quality. Specifically, we observed that the ATP binding cassette subfamily and myosin-related genes were highly methylated gene sets, and generation of neurons, regulation of GTPase activity, ion transport and anion transport, etc., were the significant pathways related with beef tenderness. Moreover, we explored the relationship between DNA methylation and gene expression in DMRs. Some methylated genes were identified as candidate biomarkers for beef tenderness. These results provide not only novel epigenetic information associated with beef quality but offer more significant insights into meat science, which will further help us explore the mechanism of muscle biology.